1994
DOI: 10.1200/jco.1994.12.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Sustained regression of a primary choroidal melanoma under the influence of a therapeutic melanoma vaccine.

Abstract: Active specific immunotherapy with cutaneous melanoma lysates has caused a clinically useful protracted regression of a primary choroidal melanoma in an elderly patient in whom surgery and radiation therapy were contraindicated. This may represent the first case of a primary choroidal melanoma, and perhaps the only primary tumor, successfully treated with systemic immunotherapy alone. A formal trial of active specific immunotherapy for primary choroidal melanoma in selected patients may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Trials, usually consisting of a small number of patients, have investigated non‐specific tumour vaccines, using methanol‐extracted residue of bacilli Calmette‐Guérin3 and interferon 2α4, although tolerated by the patients, a substantial prognostic benefit was not observed. A case report of a successful response of a primary uveal melanoma to an active specific immunotherapy consisting of lysates of cutaneous melanoma cells underlined the need for more specific approaches5. Subsequent tumour vaccines based on tumour‐specific (such as MAGE‐1 and ‐3) and tumour‐differentiation antigens (such as gp100, tyrosinase, and Melan‐A) proved more effective than the above‐mentioned non‐specific tumour vaccines in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Trials, usually consisting of a small number of patients, have investigated non‐specific tumour vaccines, using methanol‐extracted residue of bacilli Calmette‐Guérin3 and interferon 2α4, although tolerated by the patients, a substantial prognostic benefit was not observed. A case report of a successful response of a primary uveal melanoma to an active specific immunotherapy consisting of lysates of cutaneous melanoma cells underlined the need for more specific approaches5. Subsequent tumour vaccines based on tumour‐specific (such as MAGE‐1 and ‐3) and tumour‐differentiation antigens (such as gp100, tyrosinase, and Melan‐A) proved more effective than the above‐mentioned non‐specific tumour vaccines in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies utilizing the Melacine vaccine, comprising 2 allogenic cell line lysates combined with the adjuvant DETOX (detoxified Freund's adjuvant), demonstrated similar yet somewhat more promising results 65,74. In Southwest Oncology Group's phase III randomized observation‐controlled Melacine trial of stage IIa melanoma, there was no significant benefit in RFS compared with the observation arm (hazard ratio: 0.92, P = 0.51) 75.…”
Section: Melanoma Vaccinesmentioning
confidence: 98%
“…It is challenged for the predominantly immunosuppressive phenotype of tumor cells. Mitchell et al [40] reported regression of a large primary choroidal melanoma after treatment with a whole cell-based vaccine. The vaccine, called Melacine, consisted of lysates of two human cutaneous melanoma cell lines administered with immunologic adjuvant Detox.…”
Section: Whole Cell-based Vaccinesmentioning
confidence: 99%